Una nueva especie de Centrosema (DC.) Benth. (Leguminosae: Papilionoideae) del Orinoco - Schultze-Kraft, Rainer; Williams, R.J. (1990)
A new species of Centrosema is described and named C. tetragonolobum. It occurs in the region of the Orinoco river between latitudes 42 and 62 N in the Comisaría del Vichada, Colombia, and the Territorio Federal Amazonas, Venezuela. Characteristic features of the species are winged pods, chartaceous to coriaceous leaves, and an erect-climbing growth habit